Field Placement and the Impact of Financial Stress on Social Work and Human Service Students. Issue 4 (1st October 2016) - Johnstone, Eleesa; Brough, Mark; Crane, Phil; Marston, Greg; Correa-Velez, Ignacio
ABSTRACT: While significant research has been undertaken exploring the pedagogical benefits of undertaking lengthy social work and human services field placements, there has been very little consideration given to the potential financial stress involved for students. This study sought to address this knowledge gap. Research was conducted in 2014 using quantitative and qualitative methods with students and academic and professional staff from six Queensland universities. The findings show a significant relationship between unpaid placements and financial hardship, creating considerable stress for students and at times a compromised placement learning experience. The limited flexibility in requirements from professional bodies and universities for how placements are undertaken has been identified as a key contributor to financial hardship. Addressing the complexities inherent in this issue requires a collaborative effort from multiple stakeholders and should not be regarded as a problem for students to endure and manage.